Elucidating the importance of the catabolic enzyme, methionine-gamma-lyase, in stresses during Arabidopsis seed development and germination - Hacham, Yael; Shitrit, Odelia; Nisimi, Ortal; Friebach, Meital; Amir, Rachel (Frontiers in Plant Science, 2023)
The sulfur-containing essential amino acid, methionine, is a key metabolite in plant cells since it is used as a precursor for the synthesis of vital metabolites. The transcript level of methionine’s catabolic enzyme, methionine -lyase (MGL), accumulates in the seeds to a high level compared to other organs. The aim of this study was to reveal the role of MGL during seed development and germination. Using [13C]S-methylmethionine (SMM), the mobile form of methionine that is used to feed flower stalks of wild-type (WT) plants, revealed that the contents of [13C]methionine in seeds were significantly reduced when the plants underwent heat and osmotic stresses. Moreover, the levels of [13C]isoleucine, a product of MGL, significantly increased. Also, using the MGL promoter and gene fused to the GUS reporter gene, it was demonstrated that the heat stress significantly increased the protein level in the seeds. Therefore, we can conclude that MGL became active under stresses apparently to produce isoleucine, which is used as an osmoprotectant and an energy source. Transgenic Arabidopsis thaliana RNAi seeds with targeted repression of AtMGL during the late developmental stages of seeds show that the seeds did not accumulate methionine when they were grown under standard growth conditions, unlike the mgl-2, which showed a three-fold higher level of methionine. Also, when the RNAi plants developed under mid-heat stress, the level of methionine significantly increased while the content of isoleucine decreased compared to the control seeds, which strengthened the assumption that MGL is active under stress. The germination efficiency of the RNAi lines and mgl seeds were similar to their controls. However, the seeds that developed during heat or salt stress showed significantly lower germination efficiency compared to the control seeds. This implies that MGL is important to maintain the ability of the seeds to germinate. The RNAi lines and mgl seeds that developed under regular conditions, but germinated during salt or osmotic stress, exhibited a lower germination rate, suggesting an essential role of MGL also during this process. The results of this study show the important role of AtMGL in seeds under stresses.